Urgensi Islamic Worldview dalam Penguatan Keimanan, Moralitas, dan Peradaban Islam - M. Nur Saefullah; Sumiran Sumiran (TSAQOFAH, 2026)
The crisis of religious identity, moral relativism, the secularization of knowledge, and the degradation of human values have become serious challenges to the sustainability of Islamic civilization in the modern era. This condition demonstrates the importance of an epistemological framework capable of integrating the dimensions of faith, morality, knowledge, and civilizational development holistically. This study aims to analyze the urgency of the Islamic worldview as a paradigm for strengthening faith, shaping morality, and serving as the foundation for the development of Islamic civilization. This study employed a qualitative approach using the library research method. Data were obtained from primary and secondary literature discussing the Islamic worldview, Islamic educational philosophy, Islamic epistemology, and the thought of contemporary Muslim scholars. The data were analyzed descriptively and analytically through critical interpretation of various scholarly sources. The findings show that the Islamic worldview has a strategic function as an ontological, epistemological, and axiological foundation that integrates revelation, reason, and empirical experience in developing a Muslim’s worldview. This paradigm strengthens faith through the internalization of tawhid, shapes morality based on the values of the Qur’an and Sunnah, and encourages the emergence of an Islamic civilization oriented toward knowledge, justice, public benefit, and social responsibility. These findings also affirm that the Islamic worldview serves as a conceptual framework for addressing secularization, materialism, and the global ethical crisis. The conclusion of this study indicates that the Islamic worldview is an essential intellectual and spiritual foundation for strengthening Islamic identity, character formation, and the revitalization of Islamic civilization in the contemporary era. The implications of this study provide a theoretical contribution to the development of Islamic educational thought and a practical reference for curriculum development, academic research, and Islamic education policy in shaping a Muslim generation that is faithful, morally upright, knowledgeable, and contributive to the development of a sustainable civilization.